Hyalocyte origin, structure, and imaging. (4th July 2022) - Wieghofer, Peter; Engelbert, Michael; Chui, Toco YP; Rosen, Richard B; Sakamoto, Taiji; Sebag, J
ABSTRACT: Introduction: Hyalocytes have been recognized as resident tissue macrophages of the vitreous body since the mid-19 th century. Despite this, knowledge about their origin, turnover, and dynamics is limited. Areas covered: Historically, initial studies on the origin of hyalocytes used light and electron microscopies. Modern investigations across species including rodents and humans will be described. Novel imaging is now available to study human hyalocytes in vivo . The shared ontogeny with retinal microglia and their eventual interdependence as well as differences will be discussed. Expert opinion: Owing to a common origin as myeloid cells, hyalocytes and retinal microglia have similarities, but hyalocytes appear to be distinct as resident macrophages of the vitreous body.